A crucial role of miR-155 in the pathomechanism of acute kidney injury - Wang, Hui; Liao, Jian; Wang, Wei; Zhang, Jianhua (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) is one of the nonnegligible causes of mortality worldwide. It is important to understand the underlying molecular mechanism of AKI to effective therapeutic targets. miR-155 has been found to play a pivotal role in the development of AKI, while a comprehensive review on this topic is currently still lacking. Based on this review, we found that miR-155and is strongly correlated with the pathophysiological development of AKI by modulating cell apoptosis, inflammation, and proliferation. Mechanistically, miR-155 exerts a promoting function in multiple types of AKI by regulating multiple proteins or signaling pathways, such as SOCS-1, ERRFI1, SOCS-1, TRF1, CDK12, and TCF4/Wnt/β-catenin pathway. The inhibition of miR-155 has a renoprotective effect in drug- or substance-induced AKI. Therefore, drugs or biological compounds targeted by miR-155 and its pathways may recover the process of AKI by altering apoptosis, inflammation, and pyroptosis. A miRNA nanocarrier system that has already been developed could offer a novel approach to treat AKI, providing a direction for future research. Further large-scale studies are necessary to elucidate the clinical significance of miR-155 as a potential therapeutic target for multiple types of AKI.